Nodal involvement pattern in resectable lung cancer according to tumor location - Somcharoen Saeteng (2018)
The aim in this study was to define the pattern of lymph node metastasis according to the primary tumor location. In this retrospective cohort study, each of the operable patients diagnosed with lung cancer was grouped by tumor mass location. The International Association for the Study of Lung Cancer nodal chart with stations and zones, established in 2009, was used to define lymph node levels. From 2006 to 2010, 197 patients underwent a lobectomy with systematic nodal resection for primary lung cancer at Chiang Mai University Hospital. There were 123 male and 74 female patients, with ages ranging from 16-85 years old and an average age of 61.31. Analyses of tumor location, histology type, and nodal metastasis were performed. The locations were the right upper lobe in 63 patients (31.98%), the right middle lobe in 18 patients (9.14%), the right lower lobe in 30 patients (15.23%), the left upper lobe in 55 patients (27.92%), the left lower lobe in 16 patients (8.12%), and mixed lobes (more than one lobe) in 15 patients (7.61%). The mean tumor size was 4.45 cm in diameter (range 1.2-16.5 cm). Adenocarcinoma was the most common histological type, which occurred in 132 cases (67.01%), followed by squamous cell carcinoma in 41 cases (20.81%), bronchiolo alveolar cell carcinoma in nine cases (4.57%), and large cell carcinoma in seven cases (3.55%). Eighteen cases (9.6%) had skip metastasis (mediastinal lymph node metastasis without hilar node metastasis). Adenocarcinoma and intratumoral lymphatic invasion were the predictors of mediastinal lymph node metastases. There were statistically significant differences between a tumor in the right upper lobe and the right lower lobe. However, there were no statistically significant differences between tumors in the other lobes. In conclusion, tumor location is not a precise predictor of the pattern of nodal metastasis. Systematic lymph node dissection is the only way to accurately determine lymph node status. Further studies are required for evaluation and conclusions. © 2012 Saeteng et al, publisher and licensee Dove Medical Press Ltd.